2002
DOI: 10.2337/diabetes.51.12.3408
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Ghrelin Levels Are Negatively Correlated With Insulin Resistance and PAI-1, but Not With Leptin, in Obese Children and Adolescents

Abstract: Ghrelin is a novel growth hormone؊releasing peptide isolated from human and rat stomach that induces weight gain by increasing food intake and reducing fat utilization. Although recent data indicate that ghrelin is downregulated in human adult obesity, the characteristics of human obesity are heterogeneous, especially in children and adolescents, and depend on the distribution of subcutaneous and visceral fat tissue. We measured fasting plasma ghrelin concentrations by radioimmunoassay in 49 obese Japanese chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
131
4
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 24 publications
14
131
4
10
Order By: Relevance
“…Fasting insulin levels have been demonstrated to correlate negatively with fasting ghrelin levels in obese and normal -weight subjects in some studies, 10,11 whereas there was no relationship between insulin and ghrelin in other studies. 9 Insulin administration has been shown to decrease ghrelin levels.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Fasting insulin levels have been demonstrated to correlate negatively with fasting ghrelin levels in obese and normal -weight subjects in some studies, 10,11 whereas there was no relationship between insulin and ghrelin in other studies. 9 Insulin administration has been shown to decrease ghrelin levels.…”
Section: Introductionmentioning
confidence: 92%
“…Normal weight children had an age-matched BMI below 25 kg/m 2 for adults. Mean age of obese patients was 13.9 years (range 10-16), and of control children 12.3 years (range [10][11][12][13][14][15]. Patients with underlying gastrointestinal disease or endocrine disorders and patients receiving systemic glucocorticoid therapy were excluded from the study.…”
Section: Subjectsmentioning
confidence: 99%
“…In contrast to this, other studies reported correlations between ghrelin, adiponectin and leptin levels and insulin resistance. 37,40,41 These differences may be explained by the complexity of interactions, which cannot be figured out in relative moderate-sized study samples. Furthermore, diet composition influences predominately gastrointestinal hormones like ghrelin, while the other hormones are not directly influenced by diet.…”
Section: Ghrelin In Obese Children T Reinehr Et Almentioning
confidence: 98%
“…On the other hand, only weak correlations between fat mass and ghrelin levels were reported. [37][38][39] Probably, there is no direct link between adipose tissue and ghrelin levels but between factors leading to obesity and influencing ghrelin levels. For instance, a high-fat diet decreases ghrelin levels 2,3 and is thought to be one of the causes of obesity.…”
Section: Ghrelin In Obese Children T Reinehr Et Almentioning
confidence: 99%
“…Food intake and hyperglycaemia suppress ghrelin secretion [10,11] but it is controversial whether changes in glucose or insulin mediate this effect [10,12]. Several studies have shown ghrelin to be negatively associated with BMI [13][14][15] and insulin [13,15,16].…”
mentioning
confidence: 99%